Accelerometer measurement error in a randomized physical activity intervention trial in breast cancer survivors was nondifferential but attenuated the intervention effect - Laura Q. Rogers; Douglas Midthune; Kevin Dodd; Heather Bowles; Edward McAuley; Kerry S. Courneya; Brian Barrett; Spiro Razis; Gary R. Hunter; Stephen J. Carter; Raymond J. Carroll; Victor Kipnis (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Physical activity reduces morbidity and mortality risk in cancer survivors, but a meaningful proportion of this vulnerable population are physically inactive. Targeted interventions can help cancer survivors adopt a more active lifestyle, but the efficacy of these interventions must be rigorously evaluated in randomized controlled intervention trials. A major barrier to such trials involves the difficulty in obtaining unbiased estimates of physical activity in free-living conditions. Methods We conducted a randomized controlled trial of a 3-month intervention designed to increase physical activity vs. usual care in breast cancer survivors (n = 316). The primary outcome was change in physical activity as estimated by hip-worn accelerometer (MTI/Actigraph, models GT1M and GT3X). The trial included a sub-study (n = 106) wherein unbiased measures of total energy expenditure (doubly labeled water), and resting energy expenditure (indirect calorimetry) were collected. A linear mixed measurement error model characterized the structure of measurement error in accelerometry-estimated physical activity energy expenditure (PAEE), and corrected for bias in the estimated intervention effect due to measurement error. Results Bias in the accelerometer estimates was related to true PAEE (p < 0.001) and baseline body mass index (p < 0.001) but was not related to age (p = 0.13). After correcting for measurement error, the estimated intervention effect at 3 months (change from baseline in PAEE in the intervention arm minus change in the control arm) was 77 kcal/day (95% confidence interval (CI) = 31–125), compared to 48 kcal/day (95% CI = 22–75) when measurement error was ignored. These results indicate a 20% (21%) increase in PAEE kcal x d−1 (kcal x kg−1 × d−1) at month 3 relative to baseline for the corrected model vs. 14% (15%) for the uncorrected model. There was no evidence that measurement error in accelerometry-estimated PAEE was differential (differed by treatment arm) in the trial (p = 0.86). Conclusions Measurement error in accelerometer-estimated PAEE can attenuate the effect size related to intervention effects in randomized controlled trials of physical activity interventions. Sub-studies that collect unbiased measures of PAEE can be used to correct for this short-coming. Trial registration ClinicalTrials.gov; NCT00929617; registered 06/26/2009; https://clinicaltrials.gov/study/NCT00929617